Theory analysis of the Dental Hygiene Human Needs Conceptual Model. Issue 4 (9th November 2016) - MacDonald, L; Bowen, DM
Abstract: Purpose: Theories provide a structural knowing about concept relationships, practice intricacies, and intuitions and thus shape the distinct body of the profession. Capturing ways of knowing and being is essential to any professions' practice, education and research. This process defines the phenomenon of the profession – its existence or experience. Theory evaluation is a systematic criterion‐based assessment of a specific theory. This study presents a theory analysis of the Dental Hygiene Human Needs Conceptual Model (DH HNCM). Methods: Using the Walker and Avant Theory Analysis, a seven‐step process, the DH HNCM, was analysed and evaluated for its meaningfulness and contribution to dental hygiene. The steps include the following: (i) investigate the origins; (ii) examine relationships of the theory's concepts; (iii) assess the logic of the theory's structure; (iv) consider the usefulness to practice; (v) judge the generalizability; (vi) evaluate the parsimony; and (vii) appraise the testability of the theory. Findings: Human needs theory in nursing and Maslow's Hierarchy of Need Theory prompted this theory's development. The DH HNCM depicts four concepts based on the paradigm concepts of the profession: client, health/oral health, environment and dental hygiene actions, and includes validated eleven human needs that evolved overtime to eight. It is logical, simplistic, allows scientific predictions and testing, and provides a unique lens for the dental hygiene practitioner. With this model, dental hygienists have entered practice, knowing they enable clients to meet their human needs. Conclusion: For the DH HNCM, theory analysis affirmed that the model is reasonable and insightful and adds to the dental hygiene professions' epistemology and ontology.